2014
DOI: 10.5414/cn107958
|View full text |Cite
|
Sign up to set email alerts
|

Renal recovery with eculizumab in atypical hemolytic uremic syndrome following prolonged dialysis

Abstract: Hemolytic uremic syndrome (HUS) is a thrombotic microangiopathy (TMA) which encompasses hemolytic anemia, thrombocytopenia, and organ impairment. Around 10% of cases are atypical HUS (aHUS), a rare disease with poor outcomes caused by uncontrolled activation of the alternative complement pathway. This case describes a young woman with clinical manifestations compatible with TMA during childhood and adolescence who was formally diagnosed with aHUS at the age of 21. She was managed with intensive plasma exchange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 0 publications
2
31
0
2
Order By: Relevance
“…suggested that earlier initiation of eculizumab therapy was associated with better improvement of renal function [9][10][11], although some cases experienced a significant improvement in renal function after RRT of several months [9,24,25]. In our study, two of the eight patients who required RRT during the course of the disease (Patients 1, 3) started eculizumab more than one month after the onset of aHUS.…”
Section: Discussionmentioning
confidence: 55%
“…suggested that earlier initiation of eculizumab therapy was associated with better improvement of renal function [9][10][11], although some cases experienced a significant improvement in renal function after RRT of several months [9,24,25]. In our study, two of the eight patients who required RRT during the course of the disease (Patients 1, 3) started eculizumab more than one month after the onset of aHUS.…”
Section: Discussionmentioning
confidence: 55%
“…We are aware of two patients who started eculizumab after 90 and 225 days on dialysis and did not recover renal function [55,131], but also of two patients who recovered normal [132] or nearly normal [133] serum creatinine levels despite eculizumab initiation after 4 and 3.5 months on dialysis, respectively. Therefore eculizumab treatment is reasonable to consider for patients requiring dialysis for 3-4 months or even more and should be maintained for at least 3-6 months before concluding there has been no benefit.…”
Section: Education Information Cardmentioning
confidence: 93%
“…On discharge, the patient had stage 4 chronic kidney disease; at follow-up, levels of creatinine remained near normal, eGFR had increased to 35 ml /min/1.73 m 2 , and a renal biopsy found no signs of TMA. A similarly impressive degree of renal recovery has also been reported recently in a case of eculizumab therapy after >3 months of dialysis [5] , but is not seen in all cases if treatment with eculizumab is initiated too late [6] . Our case indicates that eculizumab therapy is of clinical benefit despite delayed diagnosis of aHUS and established kidney failure, an outcome also reported by Povey et al [5] .…”
Section: Discussionmentioning
confidence: 56%
“…A similarly impressive degree of renal recovery has also been reported recently in a case of eculizumab therapy after >3 months of dialysis [5] , but is not seen in all cases if treatment with eculizumab is initiated too late [6] . Our case indicates that eculizumab therapy is of clinical benefit despite delayed diagnosis of aHUS and established kidney failure, an outcome also reported by Povey et al [5] . The long-term effects of eculizumab treatment are still being established.…”
Section: Discussionmentioning
confidence: 56%